Spatial variation of structural fragility due to supershear earthquakes. (October 2022) - Karthik Reddy, K.S.K.; Veggalam, Sahithi; Somala, Surendra Nadh
Abstract: Collapse fragility of structures is studied using equipotent subshear and supershear earthquakes. Supershear earthquakes propagate at a speed faster than the shear-wave speed of the medium, thereby producing significantly different ground motion characteristics than subshear ruptures. In particular, fault parallel component dominance is established in the literature for supershear events. By considering a set of stations parallel to the strike of the fault, and another set perpendicular to the strike of the fault at various distances, fragility curves are derived as a function of distance from the fault in the near-field. In addition, the fault-parallel and fault-normal components in the near-field are applied separately to single-degree-of-freedom systems with peak-oriented modified Ibarra–Medina–Krawinkler hysteretic behaviour to characterize the component-wise differences across the subshear and supershear cases. A comparison of the median fragilities with HAZUS suggested values of similar structural systems is also presented.